2010
DOI: 10.1021/ol102269s
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Epoxidation of α-Substituted Acroleins Catalyzed by Diphenylprolinol Silyl Ether

Abstract: Asymmetric epoxidation of α-substituted acroleins with hydrogen peroxide has been catalyzed by diphenylprolinol diphenylmethylsilyl ether to afford α-substituted-β,β-unsubstituted-α,β-epoxy aldehyde with excellent enantioselectivity and the generation of a chiral quaternary carbon center. The method was applied to a short synthesis of (R)-methyl palmoxirate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 54 publications
0
24
0
3
Order By: Relevance
“…The yield, diastereo-and enantioselectivities were determined after reduction of the epoxy aldehyde 9 a to the epoxy alcohol 10 a. Since the O-silyl prolinol 4 is known to be effective for the asymmetric epoxidation of a-substituted-a,b-unsaturated alkenes, [24] the organocatalyst 4 was tried first. The epoxy aldehyde 9 a was generated as a mixture of diastereomers in a ratio of 1:1.8; subsequent aldehyde reduction provided the epoxy alcohol 10 a in 56 % yield with moderate enantioselectivity (entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield, diastereo-and enantioselectivities were determined after reduction of the epoxy aldehyde 9 a to the epoxy alcohol 10 a. Since the O-silyl prolinol 4 is known to be effective for the asymmetric epoxidation of a-substituted-a,b-unsaturated alkenes, [24] the organocatalyst 4 was tried first. The epoxy aldehyde 9 a was generated as a mixture of diastereomers in a ratio of 1:1.8; subsequent aldehyde reduction provided the epoxy alcohol 10 a in 56 % yield with moderate enantioselectivity (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…[23] In 2010, we reported the asymmetric epoxidation of a-substituted-a,b-unsaturated aldehydes by using diphenylprolinol silyl ether as the chiral catalyst. [24] This organocatalyst was developed independently by our group [25] and Jørgensen's group [26] [Scheme 1a]. Recently, we have also reported the asymmetric Michael addition of nitromethane to 2-oxoindoline-3-ylidene acetaldehydes as catalyzed by diarylprolinol silyl ether to construct all-carbon quaternary stereogenic centers with excellent enantioselectivity [Scheme 1b].…”
Section: Introductionmentioning
confidence: 99%
“…As an application, the authors developed a short synthesis of natural products (-)-(5R,6S)-norbalasubramide and (-)-(5R,6S)-balasubramide which is depicted in Scheme 48. In 2010, Hayashi et al reported a short synthesis of (R)-methyl palmoxirate, a potent oral hypoglycemic agent, based on the first successful asymmetric epoxidation of aliphatic -substituted acroleins, that was catalyzed by diphenylprolinol silyl ether 121 and H 2 O 2 as oxidant [105]. Terminal epoxide 122, bearing a quaternary stereocenter, was obtained as key intermediate in good yield (78%) and high enantioselectivity (up to 92% ee) starting from alkene 123, as shown in Scheme 49.…”
Section: Asymmetric Organocatalyzed Epoxidations As Key Stepsmentioning
confidence: 99%
“…These organocatalytic reactions paved the way to many research teams that started to work in the same field, thus developing many different catalysts types and contributing to the growth of the application potential for organocatalysis. For the enantioselective epoxidation of α and β-branched enals, Hayashi's and Jørgensen's groups independently disclosed the remarkable potential of α,α-diaryl prolinol silyl ethers (30 and 31, Figure 8a and 8b), obtaining the desired epoxide in high enantioselectivities (up to 98% ee) and excellent yields (up to 90%) [32,33]. Furthermore, both groups investigated on the reaction mechanism, hypothesising an iminium ion covalent catalysis.…”
Section: Covalent Organocatalysismentioning
confidence: 99%
“…For this reason, many of such catalysts are also called bifunctional. Noteworthy examples of bifunctional non-covalent organocatalysts are the Soós thiourea (32) and diphenyl prolinol (33), depicted in Figure 10 [38]. Both of these catalysts bear H-bond donor groups and a Brønsted base functionality [39].…”
Section: Non-covalent Organocatalysismentioning
confidence: 99%